Anterior Knee Pain in Children and Adolescents: Overview and Management - Slotkin, Steven; Thome, Andrew; Ricketts, Cassandra; Georgiadis, Andrew; Cruz, Aristides I., Jr; Seeley, Mark (The Journal of Knee Surgery, 2018)
Anterior knee pain (AKP) is a common presenting complaint for pediatricians and orthopaedic surgeons and is often seen in young athletes. AKP is multifactorial and has a broad differential diagnosis. The growth changes, biomechanics, and anatomy around the knee add to the complexity of diagnosis and treatment of AKP. Common causes of AKP include Osgood–Schlatter's disease, patellar tendinitis, and patellofemoral instability. In the diagnosis of AKP, it is important to rule out serious and morbid causes of pain, including infection and tumor. It is crucial to complete a detailed history and physical examination and obtain appropriate imaging studies. In general, the majority of patients will respond to nonoperative measures targeted to correct neuromuscular control and kinetic chain dysfunction.
Keywords: pediatrics; knee pain; patellofemoral instability; patellofemoral syndrome; Osgood–Schlatter's disease